(untitled) (Indonesian Journal of Agrarian Law, 2026)
The Comprehensive Systematic Land Registration (PTSL) program was designed to ensure legal certainty; however, its implementation regarding irregularly shaped plots in Tanjungmojo Village demonstrates that disputes can still arise due to physical control on the ground that does not align with established boundaries. This article aims to analyze the factors causing post-PTSL disputes over irregularly shaped land and to formulate strategies for preventing future disputes over village assets. This study employs an empirical legal method with a descriptive-analytical approach through interviews and field observations of the subject of Land Use Certificate No. 00014. The findings reveal that the dispute arose due to residents’ unauthorized physical occupation of approximately 477 m² following the certificate’s issuance, which was not accompanied by optimal physical boundary demarcation. It is concluded that legal certainty through the PTSL program does not rely solely on administrative data but also on the control of physical conditions on the ground. As a recommendation, strengthening the supervision and maintenance of boundary markers is necessary to prevent future disputes.